THE USE OF COMMUNICATIVE APPROACH IN TEACHING READING DESCRIPTIVE TEXT - Anna Robiana (IKIP Siliwangi, 2020)
Reading is central to learning process, by reading people can gain important information in this millennial era. Study reading aims to develop the reading skills that you need to find information quickly, to identify what is important in a text, to compare different sources of information and to read critically. The aim of this experimental research is to investigate the effect of communicative approach on reading competencies of 10th grade students of SMK SEHATI in the academic year of 2018/2019. It is about 60 pupilss were assigned as sample through random sampling. Data of student’s reading competencies were collected by using multiple choice of descriptive text test. The result shows there is significant effect at student’s reading comprehension. Keywords: Communicative Approach, Performance Assessment, Reading Competency